Analysis Of Corporate Actions And Effect On Stock Trading The Indonesia Stock Exchange - Fitriana Fitriana; Tahmat Tahmat; Abang Firdaus; Iskandar Ahmaddien (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2019)
This study aims to look at the effect of the corporate action against trading on the Stock Exchange be something interesting to do research on five companies that perform corporate actions. Data were analyzed using descriptive methods and comparative analysis of the event study method with a different test two parties. Event windows use 15 days prior to the corporate action and 15 days after the corporate action. Results of research on five companies that perform corporate actions earned actions stock buy-backs, stock-dividend and stock split no significant effect on actual returns after the announcement date. On the trading frequency, action stock-buyback have significant differences, whereas stock dividend and stock-split not. On average trading value, action stock-dividend and stock-buyback not any significant difference, while stock-split showed a significant difference. The study results are not normal events of their return on stock dividends 7 days after the date of announcement of the action stock-split-return normal not occur on days 3 and 4, while on the corporate action buy-back not occur. Stock-dividend while the information content contained in stock-split and buy-back did not show a significant investor reaction.